The Otherworldly Counter-Discourse of Yŏmbul pogwŏnmun: An Eighteenth-century Pure Land Text - Walraven, Boudewijn (Journal of Korean religions, 2015)
Although Pure Land Buddhism had been known in Korea for more than a millennium, the repeated publication throughout the eighteenth century of woodblock editions of Yŏmbul pogwŏnmun (Exhortation to universally practice the invocation of the Buddha [Amitābha]) with text in both hanmun and the vernacular, presented a quantum leap in the dissemination of Pure Land teachings and of a Buddhist vision of life and the afterlife that in several ways challenged the Confucian Weltanschauung. Although the text endorsed Confucian social values, it effectively constituted a counter-discourse to Confucianism by denying the importance of this world and by emphasizing preparations for the afterlife, which would determine whether after death one would proceed to one of the terrifying hells or to the World of Ultimate Bliss. This otherworldly orientation to the hereafter, with its contrast between hell and the paradise of Amitābha, may have facilitated the acceptance of Catholicism in the late eighteenth and early nineteenth century, particularly among women. Yŏmbul pogwŏnmun encouraged a literal belief in rebirth in the paradise of Amitābha, but the Sŏn masters who propagated the mindful invocation of Amitābha (yŏmbul) tended to have a more sophisticated concept of the practice, regarding it as a way to realize one’s buddha-nature in the here and now.